Coloduodenal Fistula: The Role of MDCT on Diagnosing a Rare Entity - Giordano Rafael Tronco Alves; John Neoptolemos; Natalia Henz Concatto; Bruno Hochhegger; Klaus Loureiro Irion (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2015)
Coloduodenal fistula is a very infrequent complication, which can arise from both benign and malignant  diseases. It consists in a pathological communication between the lumen of the colon and duodenum. The onset of signs and symptoms is generally sub-acute, and the majority of the patients will present with a non-specific abdominal pain, diarrhoea, nausea and vomiting [1]. Nevertheless, the clinical presentation may vary significantly - depending on the site of fistulisation - and some cases may never be diagnosed. When not clinically suspected, cross-sectional imaging studies can be the only tool to suggest the diagnosis and provide information necessary for deciding among therapeutic options [2]. In this article, we report a case of coloduodenal fistula arising from a colonic malignancy, diagnosed by multi-detector computed tomography scan (MDCT). A brief discussion regarding the condition and its diagnostic challenges is presented.